Cancer of Unknown Primary (CUP): genetic evidence for a novel nosological entity? A case report - Silvia Benvenuti; Melissa Milan; Elena Geuna; Alberto Pisacane; Rebecca Senetta; Gennaro Gambardella; Giulia M Stella; Filippo Montemurro; Anna Sapino; Carla Boccaccio; Paolo M Comoglio (EMBO Molecular Medicine, 2020)
Abstract Cancer of unknown primary (CUP) is an obscure disease characterized by multiple metastases in the absence of a primary tumor. No consensus has been reached whether CUPs are simply generated from cancers that cannot be detected or whether they are the manifestation of a still unknown nosological entity. Here, we report the complete expression and genetic analysis of multiple synchronous metastases harvested at warm autopsy of a patient with CUP. The expression profiles were remarkably similar and astonishingly singular. The whole exome analysis yielded a high number of mutations present in all metastases (fully shared), additional mutations (partially shared) accumulated one after another in a series, and few private mutations were unique to each metastasis. Surprisingly, the phylogenetic trajectory linking CUP metastases was atypical, depicting a common “stream”, sprouting a series of linear “brooks”, at variance from the extensive branched evolution observed in metastases from most cancers of known origin. The distinctive genetic and evolutionary features depicted suggest that CUP is a novel nosological entity.